Implementation of Protection of Wage Rights for Workers in The Micro, Small, And Medium Enterprise (MSMEs) Sector - Djaena, Oktofina; Samangun, Christina; Siswani, Carina Budi (Golden Ratio of Law and Social Policy Review, 2025)
Wages are a basic worker's right that must be protected by the state as a form of social justice and labor protection. This article examines the implementation of wage protection for workers in the Micro, Small, and Medium Enterprises (MSMEs) sector in Manokwari Regency, focusing on the effectiveness of regulations and the oversight role of local governments. The research methods used are normative and empirical juridical, through an analysis of the provisions of Law Number 6 of 2023 concerning Job Creation, Government Regulation Number 36 of 2021 concerning Wages, and West Papua Provincial Regulation Number 6 of 2022 concerning Manpower Implementation. The study results indicate that legal protection for MSME workers has been regulated normatively, but its implementation still faces structural and cultural obstacles, including weak legal awareness among MSME actors and limited labor supervision. The Manpower Office holds a strategic position in realizing wage protection, but requires strengthening its supervision system and digitizing labor services. This research recommends increasing the capacity of MSMEs, optimizing technology-based monitoring mechanisms, and fostering multi-sector collaboration to ensure the fulfillment of wage rights fairly and sustainably.